Inhibition of Polyphenoloxidase and Melanosis in Pacific White Shrimp (Litopenaeus vannamei) by Phenolic Compounds - Nilesh Prakash Nirmal (Prince of Songkla University, 2016)
Thesis (Ph.D., Food Science and Technology)--Prince of Songkla University, 2011